Geology and Resource Potential of the Congo Basin 2014
DOI: 10.1007/978-3-642-29482-2_14
|View full text |Cite
|
Sign up to set email alerts
|

Cenozoic Landscape Evolution in and Around the Congo Basin: Constraints from Sediments and Planation Surfaces

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 59 publications
0
39
0
Order By: Relevance
“…The last upwarp segment (IV) relates to the South Atlantic margin. Its considerable width (up to more than 500 km) and the uplift it has undergone during the Neogene (Guillocheau et al, 2015) suggest at least a recent mantle support. Rouby et al (2013) have shown that flexure-related rift shoulders of a passive margin are often eroded away 10-20 m.y.…”
Section: Long-wavelength Deformation Marginal Upwarps and Sedimentamentioning
confidence: 99%
“…The last upwarp segment (IV) relates to the South Atlantic margin. Its considerable width (up to more than 500 km) and the uplift it has undergone during the Neogene (Guillocheau et al, 2015) suggest at least a recent mantle support. Rouby et al (2013) have shown that flexure-related rift shoulders of a passive margin are often eroded away 10-20 m.y.…”
Section: Long-wavelength Deformation Marginal Upwarps and Sedimentamentioning
confidence: 99%
“…High Sr isotope ratios are typical of rivers draining the Archean and Proterozoic rocks constituting the border of the Congo Basin [ de Wit and Linol , ]. By contrast, the low Sr isotope ratios are characteristic of the sedimentary region at the center of the Congo Basin [ Negrel et al ., ; Guillocheau et al ., ]. One sample significantly deviates from the calculated mixing trend which can be attributed to the natural heterogeneity in terms of Sr isotope ratios of the Congo River tributaries draining the outer parts of the Congo Basin [ Negrel et al ., ] (Figure a).…”
Section: Discussionmentioning
confidence: 99%
“…These rivers represent the regional base level and have particularly low dissolved and suspended loads. Geomorphologic analyses of the planation surfaces [ Guillocheau et al ., ] indicate that the present‐day topography of the Congo Basin derives from differential uplift, less pronounced in the central basin, and higher in the surrounding areas. Conversely, dynamic topographic models show that the Cuvette Centrale results from the subsidence of the Congo Basin over the past 30 Myr in response to mantle convective drawdown [ Moucha and Forte , ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations